Assessing implementation fidelity in the First Episode Rapid Early Intervention for Eating Disorders service model. Issue 3 (7th May 2021) - Richards, Katie L.; Flynn, Michaela; Austin, Amelia; Lang, Katie; Allen, Karina L.; Bassi, Ranjeet; Brady, Gabrielle; Brown, Amy; Connan, Frances; Franklin-Smith, Mary; Glennon, Danielle; Grant, Nina; et al.
Abstract : Background: The First Episode Rapid Early Intervention for Eating Disorders (FREED) service model is associated with significant reductions in wait times and improved clinical outcomes for emerging adults with recent-onset eating disorders. An understanding of how FREED is implemented is a necessary precondition to enable an attribution of these findings to key components of the model, namely the wait-time targets and care package. Aims: This study evaluated fidelity to the FREED service model during the multicentre FREED-Up study. Method: Participants were 259 emerging adults (aged 16–25 years) with an eating disorder of <3 years duration, offered treatment through the FREED care pathway. Patient journey records documented patient care from screening to end of treatment. Adherence to wait-time targets (engagement call within 48 h, assessment within 2 weeks, treatment within 4 weeks) and care package, and differences in adherence across diagnosis and treatment group were examined. Results: There were significant increases (16–40%) in adherence to the wait-time targets following the introduction of FREED, irrespective of diagnosis. Receiving FREED under optimal conditions also increased adherence to the targets. Care package use differed by component and diagnosis. The most used care package activities were psychoeducation and dietary change. Attention to transitions was less well used. Conclusions: This study provides an indication of adherence levels to key components of the FREED model. These adherence rates can tentatively be considered as clinically meaningful thresholds. Results highlight aspects of the model and its implementation that warrant future examination.